118k views
8 votes
How to solve -2(-4f+5)=-7+2f-9

User Simon Degn
by
5.3k points

2 Answers

10 votes

Answer:


f=(3)/(5)

Explanation:


-2(4f+5)=-7+2f-9

First, use PEMDAS to distribute the -2 to the parenthesis.


-8f -10 = -7+2f -9

Combine like terms on the right side.


-8f - 10 = -16+2f

Now, you may either subtract the f's or the constants. I'll subtract the constants first, meaning I will add 10 to both sides.


-8f = -6 + 2f

Now subtract the 2f from both sides.


-10f = -6

Divide both sides by 10.


f = (-6)/(-10)

Simplify.


f = (3)/(5)

User Gamo
by
4.7k points
3 votes

Answer:

The value of f:


  • f=-1

Explanation:

Given the expression


-2\left(-4f+5\right)=-7+2f-9

Group like terms


-2\left(-4f+5\right)=2f-7-9

Subtract the numbers: -7-9=-16


-2\left(-4f+5\right)=2f-16

Expand: -2(-4f + 5) = 8f - 10


8f-10=2f-16

Add 10 to both sides


8f-10+10=2f-16+10

Simplify


8f=2f-6

Subtract 2f from both sides


8f-2f=2f-6-2f

Simplify


6f=-6

Divide both sides by 6


(6f)/(6)=(-6)/(6)

Simplify


f=-1

Therefore, the value of f:


  • f=-1
User AbeEstrada
by
4.9k points